Perception of Nigerian SMEs on electronic data interchange adoption - Shehu Musawa, Maikudi (2013)
The wide adoption of electronic data interchange (EDI) by the SMEs is important for the success of the technology. A review of past EDI adoption literature indicates that past studies have focused mainly on large businesses. With the advance of technology, SMEs businesses are now able to enjoy the benefits of EDI. SMEs businesses are the backbone of the economy in Nigeria, despite these facts, there are relatively no identified studies on perception of EDI adoption among the Nigerian SMEs. A conceptual model is then proposed to address the above issues. The model may help Nigerians SMEs to achieve higher impacts on their businesses from the adoption of EDI and may also provide strategic roadmap for SMEs in other African countries. Using a technology, organization, and environment framework, this study tested a perception base model against the data collected from 204 SMEs firms in Nigeria. Four factors that were found to be significant in the SMEs EDI adoption were direct benefits, indirect benefits, financial resources, and external pressure to adopt EDI. The results of this study could provide insight into unique factors that drive EDI adoption by SMEs in Nigeria and serve as a guide to policy initiatives to the SMEs owner managers. Key words: Technology adoption, EDI technology, Nigerian SMEs.